Die Funktion des Briefes in Hölderlins Poetologie und ihre Positionierung im Hinblick auf die Briefkultur des 18. Jahrhunderts (Studia theodisca, 2017)
Writing letters is to Hölderlin uttering ideas in a vivid general interesting manner. This is for him both a livening and spiritualizing artistic activity, which utters words to that effect in an equilibrium of mind and life. An endless beautiful reflection underlies this activity and finds utterance in a poetical prose, in which the endless form coalesces with the endless material. Hölderlin’s letters, in particular the letters in lyrical prose in Hyperion, give evidence for the expressly and sensuous art of this coalescing.